Chinese economic development and the environment - Managi, Shunsuke; Kaneko, Shinji; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2009)
Over the past two decades, China has become an economic powerhouse. However, as the world's largest producer of CO2 emissions, the scale and seriousness of China's environmental problems are clearly evident. This pioneering book provides an economic analysis of the significant environmental and energy problems facing China in the 21st century.
Introduction : economic growth and the environment -- Environmental Kuznets curve -- Efficiency in environmental management -- Wastewater, waste gas and solid waste -- Foreign direct investment and environmental policies -- Increasing returns to pollution abatement -- Causal direction between pollution abatement and environmental efficiency -- Water and agriculture -- Iron and steel industry -- Stagnancy of energy-related COb2 (Bemissions -- Energy supply-side and demand-side effects -- Experts' judgment on the future perspective -- Conclusion.s
Includes bibliographical references and index.
Keywords: Economic development -- Environmental aspects -- China; Environmental policy -- China; Energy policy -- China; Environmental protection -- China; Sustainable development -- China; Electronic books